Large eddy simulation of a turbulent flow in a 5 x 5 rod bundle with a mixing vane spacer grid - Lu, Chuan; Du, Zhaohui (Frontiers in Energy Research, 2024)
In fuel assemblies of pressurized water reactors (PWRs), mixing-vane spacer grids are extensively employed to array fuel rods and enhance inter- and intra-subchannel mixing. The turbulent flow downstream of spacer grids is essential knowledge to support the design of spacer grids and mixing vanes. As a high-fidelity approach for turbulence simulation, large eddy simulation (LES) results are assessed with the high-resolution flow field measured with particle image velocimetry (PIV). The LES results reveal a mixing vane effect on vortex structures and Reynolds stresses. The mechanism of vortex generation at the mixing vanes and the development downstream of the spacer grid are visualized by the Q-criterion. The distributions of the root mean square fluctuating velocity and Reynolds stresses decay rapidly downstream of the spacer grid. The secondary flow intensity downstream of the spacer grid predicted by LES is evaluated and follows an exponentially decaying law with distance from the spacer grid.